Elevating high-density lipoprotein cholesterol in apolipoprotein E-deficient mice remodels advanced atherosclerotic lesions by decreasing macrophage and increasing smooth muscle cell content. - Rong, J; Li, J; Reis, E; Choudhury, R; Dansky, H; Elmalem, V; Fallon, J; Breslow, J; Fisher, E (2001)
BACKGROUND: HDL cholesterol levels are inversely correlated with coronary heart disease risk in humans, and in animal studies, HDL elevation decreases formation and progression of foam-cell lesions. The potential for HDL to affect preexisting advanced atherosclerotic lesions is not known. To approach this issue, we used a novel mouse aortic transplantation model. METHODS AND RESULTS: ApoE-deficient (EKO) mice were fed a Western-type diet for 6 months, and thoracic aortic segments containing advanced lesions replaced segments of the abdominal aorta of 4-month-old EKO syngeneic mice not expressing (plasma HDL cholesterol approximately 26 mg/dL) or expressing (HDL approximately 64 mg/dL) a human apoAI (hAI) transgene. Both types of recipients had comparable non-HDL cholesterol levels. Five months after transplantation, mice were killed and grafts analyzed. Compared with lesion area in pretransplant mice (0.14+/-0.04 mm(2), mean+/-SEM), there was progression in the EKO recipients (0.39+/-0.06 mm(2), P<0.01). Compared with EKO recipients, hAI/EKO recipients had retarded progression (0.24+/-0.04 mm(2), P<0.05). Immunostaining for CD68 and other macrophage-associated proteins, monocyte chemoattractant protein-1, acyl coenzyme A:cholesterol acyltransferase, and tissue factor, in lesions of pretransplant and EKO recipient mice showed abundant macrophages. In contrast, compared with any other group, lesional macrophage area in hAI/EKO mice decreased >80% (P<0.003), and smooth muscle cell content (alpha-actin staining) increased >300% (P<0.006). The decrease in macrophages and increase in smooth muscle cells was primarily in the superficial subendothelial layer. CONCLUSIONS: Increasing HDL cholesterol levels in EKO mice retards progression of advanced atherosclerotic lesions and remodels them to a more stable-appearing phenotype.